ATMOSFER TOKO SEBAGAI PENDORONG IMPULSE BUYING - Ni Made Dhian Rani Yulianti; Joshua Putra Wikondo (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2019)
This research is based on the interest of researcher in the development and competition of the retail business which is very rapidly developing in the era of globalization where Store Atmosphere, Hedonic Shopping Motivation and Impulse Buying are important in the development of the retail business. The author's purpose in conducting this research is to nd out the inuence of store atmosphere on impulse buying, to nd out the effect of store atmosphere on hedonic shopping, to determine the inuence of hedonic shopping on impulse buying and to determine the inuence of store atmosphere on impulse buying through hedonic shopping motivation. Data that has been obtained through questionnaires to 70 respondents were analyzed by path analysis using SmartPLS V3.0 software for Windows. Based on the results of data analysis that has been taken, Store Atmosphere has a positive and signicant inuence on Hedonic Shopping Motivation, Store Atmosphere has a positive and signicant inuence on Impulse Buying, Hedonic Shopping Motivation has a positive and signicant inuence on impulse buying and Store Atmosphere has a positive inuence and signicant impact on Impulse Buying through Hedonic Shopping Motivation so that all hypotheses from this study are proven.